Instrumental and Expressive Education: Identifying the Education Interests of the Institutionalized Elderly - Radcliffe, Mary Louise (Canadian Journal of Counselling and Psychotherapy, 2011)
This research indicates that 86% of the elderly, aged 60 to 98, residing in a long-term care facility, do not believe that they are too old to learn. Interest in ongoing learning is focused on topics which are designed to enhance enjoyment rather than those based on mastery of skills.